Designing an Evaluation model of Performance based Budgeting Software through fuzzy Dematel and Analytic Hierarchical Process - Ronak Kiani; Adel Azar; Karim Bayat (پژوهش‌های مدیریت عمومی, 2021)
Extended Abstract Abstract Performance-based budgeting is an integral part of government organizations, whose goal is to achieve more efficient and effective implementation than management and performance budgeting in line with public duties, higher quality of public services, reduction of government and staff costs. is. It is necessary to reform the budget process towards performance-based budgeting, selecting software based on strategic planning, measuring performance and aligning with the long-term goals of the organization. Performance-based budgeting software is one of the few rare softwares in the country, so the lack of effective criteria in choosing software makes it difficult for government agencies to waste a huge amount of money. Therefore, the need to develop and successfully implement criteria in this system can improve the efficiency of the organization, manage effective budget expenditures and make it a competitive advantage for the organization by providing a basic for better software selection. This article, by studying the subject literature and software evaluation, the effective criteria for the performance-based budgeting software system with a qualitative-quantitative approach in the form of descriptive-applied research and the participation of several experts in the process of determining the criteria, 11 main criteria and 46 indicators were extracted. A conceptual model has been proposed using fuzzy dematel technique and hierarchical analysis to identify, rank, measure the importance and effectiveness of software criteria. The results indicate that the criteria for producing software, budget, security, and budget and performance reporting are of the importance and have the highest impact on other criteria. Therefore, in order to make optimal decisions and help managers and organizations in order to improve performance, special attention should be paid to these criteria. Introduction At present, competition for quality in the software market has become more important. Quality assessment plays an essential role in all aspects of software development. Better programming using budgeting allows managers to improve the financial health of their business (Foster, 2017). Performance in organizations follows a function beyond simple software, because it establishes the theory, model, processes, concepts, and goals of performance-based budgeting in organizations. One of the most important measures for the success of budgeting software is based on the performance measurement of software quality The purpose of this study is to identify effective criteria in implementing performance-based budgeting software in organizations. Since this is the first time this research has been done, it is considered a new topic. Theoretical framework Evaluating and selecting a software system that meets an organization's needs is a complex aspect of the software engineering process (Wolski, Walter, Kupiński, Chojnacki, 2018). There are many software evaluation models. One of the factors influencing the implementation of performance-based budgeting is information technology. This factor alone is affected by the organization's obligation to implement performance-based budgeting (Azar & Amirkhani, 2014). PBB software, in addition to helping managers evaluate performance and control resources and costs in the organization can help measure the achievement of organizational strategies and long-term and short-term goals. PBB software as a set of support capabilities Operational tasks, including budgeting and planning, performance measurement, and appropriate reporting, are considered Methodology The present research is applied in terms of purpose and descriptive and causal in terms of method. The statistical population of this study includes experts and professors in two groups: policymakers and developers, who were selected by snowball sampling.  The number of statistical sample members is 4 of these people who have relevant technical knowledge, doctoral degree and also have more than 5 years of work experience in the field of performance-based budgeting software system. Data collection has been collected through library studies, searching on scientific sites and reviewing existing scientific texts on software evaluation methods and decision-making techniques. Discussion and Results Findings based on Demtel's technique include 11 main criteria of performance-based budgeting software calculated by Excel software: Flexibility, maintenance, efficiency, performance management, budget, budget reporting, reliability, price Finished, usable, secure and software manufacturer The weights obtained in relation to software indicators such as integration and smooth communication between software modules, software upgrade capability, observance of user access levels and software encryption and related documents indicate more importance than other indicators. Conclusion Criteria for reporting budget, budget, usability and security are the most important. Software manufacturers, budget, security, and budget reporting have the most effective indicators and the strongest relationshp with other metrics. The most influential indicators were flexibility, maintenance capability and efficiency. Managers need to identify the current budget, capital budget, and assets to determine their expectations of the software and make the budget as transparent as possible. Software security is the Achilles heel of software systems. To reduce the security risks posed by software, engineers need to take a disciplinary approach based on infrastructure, levels of access to information, accuracy and integrity of information, and confidentiality of information. Security is one of the most important concerns of managers. Manufacturers should prioritize software upgrades according to the organization's needs and ensure smooth integration and communication between modules.